The Prevalence of Psychiatric Co-Morbidities is Alarmingly High for Patients undergoing Orthopedic Sports Medicine Procedures. Issue 7 (31st July 2020) - Khazi, Zain; Duchman, Kyle; Wolf, Brian; Westermann, Robert; Baron, Jacqueline
Objectives: The prevalence of preoperative psychiatric comorbidities and substance abuse disorders among patients undergoing common sports medicine operative procedures has yet to be delineated. This study investigated the prevalence and influence of preoperative psychiatric comorbidities on costs following ten common orthopaedic sports medicine procedures. Methods: The Humana Inc. administrative claims database was accessed using the PearlDiver research program to identify patients undergoing ten common Sports Medicine interventions (Starman et al, , JBJS, 2010) (Table 1): ACL reconstruction; PCL reconstruction; MCL repair/reconstruction; achilles reconstruction; rotator cuff repair; meniscal repair/reconstruction; hip arthroscopy; arthroscopic shoulder labral repair; patellofemoral instability; and shoulder instability repair from 2007-2017q1. Patients were stratified by preoperative diagnoses (Table 2) of depression, anxiety, bipolar disorder, or schizophrenia. Cohorts included patients with ≥1 psychiatric comorbidity [Psychiatric] vs. those without psychiatric comorbidities [No Psychiatric]. Patients were assessed for diagnosed substance-abuse disorders, including alcohol use disorder, opioid use disorder, or tobacco use disorder. Temporal trends from 2007-2016 [rate of ≥1 psychiatric co-morbidity] were assessed per 100, 000 persons utilizing linear regression and ANOVA regression analyses. Differences in costs across groups were assessed utilizing MannWhitney tests using the R statistical tool housed within the PearlDiver research program. Results: The prevalence of ≥1 psychiatric co-morbidity [Psychiatric] in the whole database was 10.31% versus 21.21% amongst those patients undergoing one of the ten common orthopaedic interventions. Rotator cuff repair (28%), meniscus repair (24.58%), and hip arthroscopy with concomitant labral repair (26.27%) had the highest prevalence of patients with ≥1 psychiatric co-morbidity diagnosed preoperatively. The presence of ≥1 psychiatric co-morbidities diagnosed preoperatively versus those without psychiatric co-morbidities was associated with increased per capita patient costs (all p<0.01) for all procedures (Table 2). The rate of psychiatric co-morbidities remained elevated across all ten conditions (all p>0.05, Table 5-6; Figure 1) from 2007-2016. Conclusion: The prevalence of preoperatively diagnosed psychiatric comorbidities among patients undergoing orthopaedic sports medicine procedures (21.21%) is alarmingly high and nearly two times higher than baseline rates reported in the database. The presence of psychiatric comorbidities preoperatively was associated with increased costs for all investigated orthopaedic sports medicine procedures, warranting further investigation. 1Quality and Content of Internet-Based Information for Ten Common Orthopaedic Sports Medicine Diagnoses. Starman, J.S., Gettys, F.K., Capo, J.A., Fleischli, J.E., Norton, H.J. and Karunakar, M.A. JBJS. (92)1612-1618. 2010. Figure 1. Figure 2. Figure 3. Figure 4.